Mediating Role of Emotional Intelligence Between Family Communication Patterns and Achievement Motivation Among High School Students - Roya Abbasi-Asl; Habibollah Naderi; Abbas Akbari (Shiraz University of Medical Sciences, 2017)
Background: Achievement motivation is among the structures that have been attracting the attention of many researchers in the field of psychology and education. Objectives: The present study aimed at investigating the mediating role of emotional intelligence in relationship between family communication patterns and achievement motivation. Methods: In this correlational study, 291 high school students (all male) were selected from Shiraz city using the random multistage cluster sampling method. To collect data, the scale of family communication patterns, emotional intelligence and achievement motivation questionnaires were used. The research conceptual model was analyzed and assessed using the simultaneous sequential regression method and the steps proposed by Baron and Kenny. All analyses were performed using the SPSS software version 22. Results: The results showed that family conversation orientation was a positive predictor of achievement motivation (P < 0.01) and emotional intelligence (P < 0.01). Also, the results revealed that family conformity orientation was a negative predictor of achievement motivation (P < 0.01) and emotional intelligence (P < 0.01). Emotional intelligence was a positive predictor of achievement motivation (P < 0.01) and emotional intelligence played a partial mediator between family conversation orientation and conformity orientation with achievement motivation. Conclusions: According to the results of this study, increasing of conversation orientation and emotional intelligence and decreasing of conformity orientation are accompanied by increasing high school students' achievement motivation.